Feminist Legal Theory dalam Peraturan Mahkamah Agung; Studi Analisis Hukum Islam - Mahardini, Iin Aulia; Siti Aisyah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
This article aims to analyze how the feminist legal theory in the Supreme Court Regulation number 3 of 2017 concerning guidelines for adjudicating women's cases in conflict with the law (analytic study of Islamic law). In answering the problems above, the author uses library research which is guided by the processing of data obtained from several literatures. The sources of data obtained include secondary and primary data. This research approach using a qualitative approach is something that is based on a literature study by exploring scientific works that are directly related to the object being studied and analyzing in the literature that has relevance to the problem being discussed, then reviewing and then concludin. The results of this study are how then the urgency of feminist legal theory in adjudicating women's cases against the law. The series of law enforcement processes from investigation, prosecution, to trial in court must comply with the reasoning of the laws and regulations. However, conformity with statutory regulations is not enough, because often court decisions that are in accordance with statutory regulations fail to fulfill a sense of justice and do not even reach the truth of a logical truth. The general character of law formation is often not based on the experience of women and its formulation is more on the granting of power to suppress others, including against women. This is inseparable from the construction of patriarchal ideology and culture